Principles of Implementation of Transfer of Undertaking Protection of Employment (Tupe) as a Form of Legal Protection for Outsourcing Workers - Iona Febrina Simanjuntak; July Esther; Roida Nababan (PT FORMOSA CENDEKIA GLOBAL, 2025)
The Transfer of Undertaking Protection of Employment (TUPE) principle gives birth to a new legal norm that guarantees legal protection for the rights of outsourced workers. This protection is especially applicable when a job continues even though there is a change of company that carries out part of the work from another company or a labor provider company. This study uses a normative legal method, namely an approach that focuses on literature review by examining regulations and literature relevant to the problems being studied. In an effort to adjust the concept of outsourcing in accordance with the provisions of Government Regulation Number 35 of 2021, Law Number 6 of 2023 which stipulates the Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into law reaffirms the principle of protection for workers in the outsourcing scheme. With this principle, workers get legal certainty, so that they do not lose their jobs or the rights they have previously obtained. In addition, TUPE also contributes to increasing the sense of security and stability in employment relationships.